Electrolyte for alloy, polishing method and corrosion method
By using an electrolyte composed of perchloric acid, hydrochloric acid and anhydrous ethanol for electrolytic polishing and corrosion, the problems of low efficiency and poor corrosion effects of traditional polishing methods are solved, and efficient polishing and corrosion of GH3536 alloy is achieved, which significantly improves the effect of tissue analysis.
Patent Information
- Application Number
- CN202411798775.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
AI Technical Summary
The traditional vibration polishing method has high requirements for sample size, cumbersome process, long polishing time and poor effect. Especially for the GH3536 alloy formed by laser powder bed fusion, the corrosion effect of existing chemical corrosive agents is not good.
An electrolyte solution for alloys, including perchloric acid, hydrochloric acid and anhydrous ethanol, is provided to achieve efficient polishing and corrosion of the alloy by electrolytic polishing and electrolytic corrosion methods.
This method can significantly improve the polishing effect of the alloy, simplify the process, shorten the polishing time, avoid scratches and defects, and effectively corrode the precipitation phase at the grain boundary of the laser powder bed fused to form GH3536 alloy.
Smart Images

Figure CN119553347A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallographic analysis, and in particular relates to an electrolyte, a polishing method and a corrosion method for alloys. Background Art
[0002] GH3536 alloy (Hastelloy X) is a typical Ni-Cr-Fe based solid solution strengthened deformation high temperature alloy, which mainly exists in the form of Cr and Mo strengthened solid solution. GH3536 alloy exhibits excellent comprehensive properties at high temperature, such as outstanding oxidation resistance and corrosion resistance, as well as good hot and cold forming ability and weldability. This alloy has been widely used in the aerospace field at home and abroad. In my country, it is mainly used to manufacture high temperature components such as aero-engine combustion chambers, honeycomb structures, diffusers, etc. Laser powder bed fusion technology is an additive manufacturing process that uses laser to melt metal powder layer by layer to prepare three-dimensional structures. It has advantages in processing efficiency, material saving and manufacturing of functional parts with complex geometric shapes. Due to its excellent forming properties, the GH3536 alloy formed by laser powder bed fusion has played a certain role in the aerospace field.
[0003] The microstructure analysis of GH3536 alloy manufactured by traditional technology is relatively mature, and microstructures such as grains and grain boundaries can be observed through effective vibration polishing and chemical corrosion. However, the traditional vibration polishing method has high requirements on sample size, the process is cumbersome, the polishing time is long, about 2-3 hours, and the polishing effect is not good (for example, there may be residual scratches on the sample surface after polishing), which affects the results of organizational analysis; for the GH3536 alloy formed by laser powder bed fusion, because its alloy grains are small, there are more grain boundaries, it has fine grain strengthening and grain boundary strengthening effects, and the alloy itself has strong corrosion resistance, so the corrosion effect of existing chemical corrosive agents is not good, such as the precipitated phase at the grain boundary of the sample is not corroded out, and the grain boundary corrosion is not obvious. Summary of the invention
[0004] Therefore, the present invention provides an electrolyte, a polishing method and a corrosion method for alloys to solve the problem of poor polishing effect in the prior art.
[0005] In order to solve the above problems, on the one hand, the present invention provides an electrolyte for alloy, wherein the electrolyte is used for electrolytic polishing or electrolytic corrosion of the alloy; the electrolyte comprises perchloric acid, hydrochloric acid and anhydrous ethanol;
[0006] Wherein, in terms of volume, the perchloric acid is 50 to 60 parts, the hydrochloric acid is 50 to 60 parts, and the anhydrous ethanol is 400 to 480 parts.
[0007] Furthermore, in the electrolyte, the volume ratio of the perchloric acid, hydrochloric acid and anhydrous ethanol is 1:1:7.5-8.5; and / or
[0008] The mass concentration of the perchloric acid is 70% to 72%; and / or
[0009] The mass concentration of the hydrochloric acid is 36% to 38%; preferably, the hydrochloric acid is high-grade pure hydrochloric acid; and / or
[0010] The mass concentration of anhydrous ethanol is ≥ 99.7%; preferably, the anhydrous ethanol is analytical grade anhydrous ethanol; and / or
[0011] The alloy is GH3536 alloy; preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method.
[0012] In another aspect, the present invention provides a polishing method for an alloy, comprising the following steps:
[0013] placing the alloy in an electrolyte for electrolytic polishing;
[0014] The alloy is used as an anode and a nickel sheet is used as a cathode;
[0015] Preferably, the electrolyte is any one of the electrolytes for alloys described above.
[0016] Further, the alloy is GH3536 alloy;
[0017] Preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method;
[0018] Preferably, the chemical composition of the GH3536 alloy includes, by mass percentage: C: 0.05wt.%~0.15wt.%, Cr: 20.50wt.%~23.00wt.%, Co: 0.50wt.%~5.50wt.%, W: 0.2wt.%~1.00wt.%, Mo: 8.00wt.%~10.00wt.%, Al≤0.05wt.%, Ti≤0.15wt.%, Fe: 17.00wt.%~20.00wt.%, and the balance is Ni.
[0019] Furthermore, the electrolytic polishing adopts a voltage-stabilized output mode;
[0020] Preferably, the voltage is 24-28V and the current is 1.0-2.0A;
[0021] Preferably, the electrolytic polishing time is 10 to 15 seconds.
[0022] Further, the polishing method is used to perform structural analysis on the alloy; and / or
[0023] Before the electrolytic polishing step, the method further includes: cutting the alloy into a set size and then performing a grinding process;
[0024] Preferably, the set size is (15-30) mm×(15-30) mm×(15-30);
[0025] Preferably, the grinding process includes: on an automatic grinding and polishing machine, using 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, 3000 mesh sandpaper to grind the cut alloy in sequence until there is no oxide scale and scratches on the surface of the alloy.
[0026] In another aspect, the present invention provides a method for etching an alloy, comprising the following steps:
[0027] Placing the alloy in an electrolyte for electrolytic corrosion;
[0028] The alloy is used as an anode and a nickel sheet is used as a cathode;
[0029] Preferably, the electrolyte is any one of the electrolytes for alloys described above.
[0030] Further, the alloy is GH3536 alloy;
[0031] Preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method;
[0032] Preferably, the chemical composition of the GH3536 alloy includes, by mass percentage: C: 0.05wt.%~0.15wt.%, Cr: 20.50wt.%~23.00wt.%, Co: 0.50wt.%~5.50wt.%, W: 0.2wt.%~1.00wt.%, Mo: 8.00wt.%~10.00wt.%, Al≤0.05wt.%, Ti≤0.15wt.%, Fe: 17.00wt.%~20.00wt.%, and the balance is Ni.
[0033] Furthermore, the electrolytic corrosion adopts a voltage-stabilized output mode;
[0034] Preferably, the voltage is 5 to 8 V; the current is 0.5 to 0.8 A;
[0035] Preferably, the electrolytic corrosion time is 5 to 10 seconds.
[0036] Further, the corrosion method is used to perform structural analysis on the alloy; and / or
[0037] Before the electrolytic corrosion step, the method further includes: cutting the alloy into a set size, and then performing grinding and polishing in sequence;
[0038] Preferably, the set size is (15-30) mm×(15-30) mm×(15-30);
[0039] Preferably, the grinding process comprises: grinding the cut alloy on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy;
[0040] Preferably, the polishing process comprises: polishing the alloy after the grinding process on an automatic grinding and polishing machine using a water-soluble polishing paste; further preferably, the particle diameter of the water-soluble polishing paste is 2 to 3 μm.
[0041] Compared with the prior art, the present invention has at least the following beneficial effects:
[0042] 1. The present invention provides an electrolyte for alloys, the electrolyte comprising perchloric acid, hydrochloric acid and anhydrous ethanol; in the electrolyte, perchloric acid is 50-60 parts, hydrochloric acid is 50-60 parts, and anhydrous ethanol is 400-480 parts; based on the above electrolyte, perchloric acid and hydrochloric acid are used as strong acids, and the strong acid ions in the two components can produce strong corrosiveness in alcohol (anhydrous ethanol) as an electrolyte solution. During the electrolysis process, the potential difference generated can corrode the uneven positions of the sample (alloy), thereby making the sample surface smooth, thereby improving the polishing effect.
[0043] 2. On the other hand, the present invention provides a method for polishing an alloy using the above-mentioned electrolyte, comprising: placing the alloy in the electrolyte for electrolytic polishing; wherein the alloy is used as the anode and the nickel sheet is used as the cathode; based on the above-mentioned polishing method, scratch defects can be avoided on the alloy surface, thereby ensuring the polishing effect; at the same time, the polishing process is simple and the polishing time is short, about 10 to 15 seconds.
[0044] 3. Further, for the GH3536 alloy formed by laser powder bed fusion, the present invention sets the parameters of electrolytic polishing as follows: voltage of 24-28V, current of 1.0-2.0A; electrolytic polishing time of 10-15s; since the grains of the GH3536 alloy are small and there are many grain boundaries, it has fine grain strengthening and grain boundary strengthening effects, and the alloy itself has strong corrosion resistance. When the electrolytic polishing time is short and the voltage value is low, the scratches on the surface of the sample (alloy) are not completely dissolved, which is not conducive to the microstructure analysis of the alloy (for example, under the EBSD probe, a large number of defects that interfere with the surface flatness of the sample will be generated); if the polishing time is long and the voltage value is high, since the electrolyte is composed of two strong acids, an electrolytic corrosion state will occur in the later stage of electrolytic polishing, and the effect of electrolytic polishing cannot be achieved, which is not conducive to the microstructure analysis of the alloy (for example, the sample surface will turn black under the EBSD probe).
[0045] 4. In another aspect, the present invention provides a method for etching using the above electrolyte, comprising: placing an alloy in an electrolyte for electrolytic etching; wherein the alloy is used as an anode and a nickel sheet is used as a cathode; based on the above etching method, the GH3536 alloy formed by laser powder bed fusion is corroded to corrode the precipitated phase at the grain boundary, etc.
[0046] 5. Furthermore, for the GH3536 alloy formed by laser powder bed fusion, the present invention sets the parameters of electrolytic corrosion as follows: voltage of 5 to 8 V; current of 0.5 to 0.8 A; electrolytic corrosion time of 5 to 10 s; under the condition of low voltage and short corrosion time, the sample (alloy) will not reach the state of corrosion, that is, the surface of the sample is still in a polished state, and there are no grains and grain boundaries inside the sample, which is not conducive to the microstructure analysis of the alloy; if the voltage value during the electrolysis process is too high and the corrosion time is long, the potential difference formed by the anode and the cathode is high, the sample will reach the state of excessive corrosion, that is, black areas will appear on the surface of the sample, that is, the state of ablation that we can usually see in life, which is also not conducive to the microstructure analysis of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0048] Figure 1 EBSD image (300 times) of the alloy after electrolytic polishing in Example 1; wherein: (a) is the transverse structure, and (b) is the longitudinal structure;
[0049] Figure 2 EBSD image (300 times) of the alloy after vibration polishing in Comparative Example 1; wherein: (a) is the transverse structure, and (b) is the longitudinal structure;
[0050] Figure 3 EBSD image (300 times) of the alloy after electrolytic polishing in Comparative Example 4; wherein: (a) is the transverse structure, and (b) is the longitudinal structure;
[0051] Figure 4 The metallographic image (100 times) of the alloy after electrolytic corrosion in Example 4; wherein: (a) is the transverse structure, and (b) is the longitudinal structure;
[0052] Figure 5 The metallographic image (100 times) of the alloy after chemical etching in Comparative Example 5; wherein: (a) is the transverse structure, and (b) is the longitudinal structure;
[0053] Figure 6 This is the metallographic image (100 times) of the alloy after electrolytic corrosion in Comparative Example 8; wherein: (a) is the transverse structure, and (b) is the longitudinal structure. DETAILED DESCRIPTION
[0054] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0055] The invention provides an electrolyte for alloys, wherein the electrolyte is used for electrolytic polishing or electrolytic corrosion of the alloys; the electrolyte comprises perchloric acid, hydrochloric acid and anhydrous ethanol; wherein, by volume, the perchloric acid is 50 to 60 parts, the hydrochloric acid is 50 to 60 parts, and the anhydrous ethanol is 400 to 480 parts.
[0056] In some embodiments, in the electrolyte, the volume ratio of perchloric acid, hydrochloric acid, and anhydrous ethanol is 7.5 to 8.5; after taking perchloric acid, hydrochloric acid, and anhydrous ethanol according to the ratio, a glass rod is used to fully stir the solution to dissipate heat, thereby obtaining the electrolyte for the alloy;
[0057] Among them, the mass concentration of perchloric acid is 70% to 72%; the mass concentration of hydrochloric acid is 36% to 38%; preferably, the hydrochloric acid is high-grade pure hydrochloric acid; the mass concentration of anhydrous ethanol is ≥99.7%; preferably, the anhydrous ethanol is analytical grade anhydrous ethanol; the alloy is GH3536 alloy; preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method.
[0058] In another aspect, the present invention provides a polishing method for an alloy, comprising the following steps:
[0059] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is (15-30) mm×(15-30) mm×(15-30) mm;
[0060] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic polishing, and are taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte is the above-mentioned electrolyte for the alloy; other conductive and corrosion-resistant metals can also be used as cathodes.
[0061] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.05wt.% to 0.15wt.%, Cr: 20.50wt.% to 23.00wt.%, Co: 0.50wt.% to 5.50wt.%, W: 0.2wt.% to 1.00wt.%, Mo: 8.00wt.% to 10.00wt.%, Al≤0.05wt.%, Ti≤0.15wt.%, Fe: 17.00wt.% to 20.00wt.%, and the balance is Ni;
[0062] For the GH3536 alloy formed by the laser powder bed fusion method, a voltage-stabilized output mode is adopted during electropolishing; wherein the voltage is 24 to 28 V, the current is 1.0 to 2.0 A, and the electropolishing time is 10 to 15 s.
[0063] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0064] The principle of electrolytic polishing is that a thin oxide film will form on the metal surface during the electrolysis process. The formation and dissolution of this film is a dynamic equilibrium process. Compared with the uneven and scratched sample surface, the raised part of the surface is easily dissolved, while the dissolution rate of the concave part is slower. This difference in dissolution rate makes the sample surface smooth. If the polishing time is short and the voltage value is low, when the scratches on the sample surface are not completely dissolved, a large number of defects that interfere with the surface flatness of the sample will be generated under the EBSD probe, which will have an adverse effect on the microstructure analysis of the alloy; if the polishing time is long and the voltage value is high, since the electrolyte is composed of two strong acids, electrolytic corrosion will occur in the later stage of the electrolysis process, and the effect of electrolytic polishing will not be achieved. The sample surface will turn black under the EBSD probe, which will have an adverse effect on the microstructure analysis of the alloy.
[0065] The electrolytic polishing process is a process that uses electrochemical reactions to smooth and polish the metal surface. The use of the above electrolyte to electrolytically polish the laser powder bed fusion-formed GH3536 alloy can efficiently polish the GH3536 alloy, and it also serves as a reference for similar solid solution-strengthened high-temperature alloys.
[0066] In another aspect, the present invention provides a method for etching an alloy, comprising the following steps:
[0067] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; and then the alloy after the grinding treatment is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2 to 3 μm; wherein the set size is (15 to 30) mm×(15 to 30) mm×(15 to 30) mm;
[0068] The polished alloy is used as the anode to connect to the positive pole of the DC regulated power supply, and the nickel sheet is used as the cathode to connect to the negative pole of the DC regulated power supply; the anode and the cathode are immersed in the electrolyte at the same time for electrolytic corrosion, and then taken out after the end to obtain the electrolytic corrosion sample; wherein the electrolyte is the electrolyte used for the alloy mentioned above; other conductive and difficult to corrode metals can also be used as cathodes. The electrolytic corrosion is carried out in a fume hood to prevent the volatilization of perchloric acid and high-grade pure hydrochloric acid in the electrolyte from harming the experimental environment and human body.
[0069] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.05wt.% to 0.15wt.%, Cr: 20.50wt.% to 23.00wt.%, Co: 0.50wt.% to 5.50wt.%, W: 0.2wt.% to 1.00wt.%, Mo: 8.00wt.% to 10.00wt.%, Al≤0.05wt.%, Ti≤0.15wt.%, Fe: 17.00wt.% to 20.00wt.%, and the balance is Ni;
[0070] For the GH3536 alloy formed by the laser powder bed fusion method, a voltage-stabilized output mode is adopted during electrolytic corrosion, wherein the voltage is 5 to 8 V, the current is 0.5 to 0.8 A, and the electrolytic corrosion time is 5 to 10 s.
[0071] The electrolytic corrosion sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for phase analysis.
[0072] Since electrolytic corrosion usually involves a spontaneously formed electrochemical cell, that is, the anode and cathode are connected by an electrolyte, and the anode and cathode are at different points in the electrolyte, forming a potential difference, which leads to the flow of current. If the voltage value during the electrolysis process does not meet the standard, the corrosion time is short, and the potential difference formed by the anode and cathode is not enough to form a loop, that is, the current in the loop does not reach the standard that can corrode the sample, so under low voltage and short corrosion time, the sample will not reach the state of corrosion, that is, the surface of the sample is still in a polished state, and there are no grains and grain boundaries inside the sample; if the voltage value during the electrolysis process is too high, the corrosion time is long, and the potential difference formed by the anode and cathode is high, the sample will reach a state of excessive corrosion, that is, a black area will appear on the surface of the sample, that is, the state of ablation that we can usually see in life. At the same time, under the metallographic microscope and scanning electron microscope, pitting will appear inside the sample, and no precipitated phase can be found at the grain boundary, because due to excessive corrosion, the precipitated phase at the grain boundary will fall off, so the ultimate purpose of the experiment cannot be achieved.
[0073] The following is further described with reference to specific embodiments and comparative examples.
[0074] Example 1
[0075] This embodiment provides a polishing method for an alloy, comprising the following steps:
[0076] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is 15mm×15mm×15mm;
[0077] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic polishing, and are taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte includes 50 mL of perchloric acid; 50 mL of high-grade pure hydrochloric acid; and 400 mL of analytical grade anhydrous ethanol.
[0078] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0079] During electrolytic polishing, a voltage-stabilized output mode was used, wherein the voltage was 26 V, the current was 1.0 A, and the electrolytic polishing time was 15 s.
[0080] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0081] The EBSD image of the polished alloy in this embodiment is as follows: Figure 1 As shown, the grain morphology and orientation of the GH3536 alloy can be clearly shown without scratch interference; among them, the transverse structure is cellular grains, and the longitudinal structure is columnar grains.
[0082] Example 2
[0083] This embodiment provides a polishing method for an alloy, comprising the following steps:
[0084] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is 15mm×15mm×15mm;
[0085] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic polishing, and are taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte includes 55 mL of perchloric acid; 55 mL of high-grade pure hydrochloric acid; and 440 mL of analytical grade anhydrous ethanol.
[0086] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0087] During electrolytic polishing, a voltage-stabilized output mode was used, wherein the voltage was 26 V, the current was 1.0 A, and the electrolytic polishing time was 15 s.
[0088] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0089] The EBSD image of the polished alloy in this embodiment can clearly show the grain morphology and orientation of the GH3536 alloy without any scratch interference.
[0090] Example 3
[0091] This embodiment provides a polishing method for an alloy, comprising the following steps:
[0092] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is 15mm×15mm×15mm;
[0093] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic polishing, and are taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte includes 60 mL of perchloric acid; 60 mL of high-grade pure hydrochloric acid; and 480 mL of analytical grade anhydrous ethanol.
[0094] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0095] During electrolytic polishing, a voltage-stabilized output mode was used, wherein the voltage was 26 V, the current was 1.0 A, and the electrolytic polishing time was 15 s.
[0096] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0097] The EBSD image of the polished alloy in this embodiment can clearly show the grain morphology and orientation of the GH3536 alloy without any scratch interference.
[0098] Comparative Example 1
[0099] This comparative example provides a polishing method for an alloy, comprising the following steps:
[0100] Cut the alloy into the set size, and then polish the cut alloy on the automatic grinding and polishing machine with 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh sandpaper in sequence until there is no oxide scale and scratch on the surface of the alloy; and clean the polished alloy surface with alcohol or deionized water;
[0101] The polished alloy was placed in a vibration polishing instrument and subjected to vibration polishing for 4 hours to obtain a vibration polishing sample.
[0102] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0103] The vibration-polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0104] The EBSD image of the polished alloy in this comparative example is as follows Figure 2As shown, it can be seen that when the GH3536 alloy formed by laser powder bed fusion is processed by vibration polishing method, obvious scratches can be observed and the grain orientation is not clear, which affects the analysis results.
[0105] Comparative Example 2
[0106] This comparative example provides a polishing method for an alloy, comprising the following steps:
[0107] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is 15mm×15mm×15mm;
[0108] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic polishing, and are taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte includes 55 mL of perchloric acid; 55 mL of high-grade pure hydrochloric acid; and 440 mL of analytical grade anhydrous ethanol.
[0109] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0110] During electrolytic polishing, a voltage-stabilized output mode is used, wherein the voltage is 16 V, the current is 1.0 A, and the electrolytic polishing time is 5 s.
[0111] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0112] The polished alloy surface in this comparative example has residual scratches, which may cause a large number of defects that affect the experimental results under the EBSD probe. Moreover, when the electrolytic polishing process parameters (voltage, polishing time) do not meet the standards, the grains inside the alloy cannot be seen after polishing, which has an adverse effect on the final experimental results.
[0113] Comparative Example 3
[0114] This comparative example provides a polishing method for an alloy, comprising the following steps:
[0115] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is 15mm×15mm×15mm;
[0116] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic polishing, and are taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte includes 55 mL of perchloric acid; 55 mL of high-grade pure hydrochloric acid; and 440 mL of analytical grade anhydrous ethanol.
[0117] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0118] During electrolytic polishing, a voltage-stabilized output mode was used, wherein the voltage was 36 V, the current was 1.0 A, and the electrolytic polishing time was 25 s.
[0119] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0120] The surface of the alloy polished in this comparative example will have obvious traces of ablation, and will appear black under the EBSD probe, which will have an adverse effect on the experimental results; when the process parameters of electrolytic polishing (voltage, polishing time) do not meet the standards, the grains inside the alloy cannot be seen after polishing, which has an adverse effect on the final experimental results.
[0121] Comparative Example 4
[0122] This comparative example provides a polishing method for an alloy, comprising the following steps:
[0123] The alloy is cut into a set size, and then the cut alloy is polished on an automatic polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until the surface of the alloy is free of oxide scale and scratches; and the polished surface of the alloy is cleaned with alcohol or deionized water; wherein the set size is 15mm×15mm×15mm;
[0124] The polished alloy is used as an anode connected to the positive pole of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative pole of a DC regulated power supply; the anode and cathode are immersed in an electrolyte at the same time for electrolytic polishing, and taken out after completion to obtain an electrolytic polishing sample; wherein the electrolyte includes 400 mL of perchloric acid; 50 mL of high-grade pure hydrochloric acid; 50 mL of analytical grade anhydrous ethanol. That is, the ratio of perchloric acid: high-grade pure hydrochloric acid: analytical grade anhydrous ethanol is 8:1:1
[0125] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0126] During electrolytic polishing, a voltage-stabilized output mode was used, wherein the voltage was 26 V, the current was 1.0 A, and the electrolytic polishing time was 15 s.
[0127] The electrolytically polished sample is cleaned with alcohol and blown dry to obtain a polished alloy, which can be used for EBSD (backscattered electron diffraction) analysis.
[0128] The EBSD image of the polished alloy in this embodiment is as follows: Figure 3 As shown in the figure, the image detected by EBSD is black. The increase in the proportion of strong acid in the front electrolyte will corrode the surface of the sample without forming a thin film. This will produce black in the EBSD image, affecting the experimental results.
[0129] Example 4
[0130] This embodiment provides a corrosion method for alloys, comprising the following steps:
[0131] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0132] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic corrosion, and are taken out after the end to obtain an electrolytic corrosion sample; wherein the electrolyte includes 50 mL of perchloric acid; 50 mL of high-grade pure hydrochloric acid; and 400 mL of analytical grade anhydrous ethanol.
[0133] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0134] During electrolytic corrosion, a voltage-stabilized output mode is used, wherein the voltage is 6V, the current is 0.6A, and the electrolytic corrosion time is 10s.
[0135] The electrolytic corrosion sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0136] The scanning image of the alloy after etching in this embodiment is as follows: Figure 4 As shown, the organizational morphology of the GH3536 alloy can be clearly seen; among them, the transverse organization is an obvious scanning path overlap track, and the longitudinal organization is a fish-scale molten pool.
[0137] Example 5
[0138] This embodiment provides a corrosion method for alloys, comprising the following steps:
[0139] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0140] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic corrosion, and are taken out after the end to obtain an electrolytic corrosion sample; wherein the electrolyte includes 55 mL of perchloric acid; 55 mL of high-grade pure hydrochloric acid; and 440 mL of analytical grade anhydrous ethanol.
[0141] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0142] During electrolytic corrosion, a voltage-stabilized output mode is used, wherein the voltage is 6V, the current is 0.6A, and the electrolytic corrosion time is 10s.
[0143] The electrolytic corrosion sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0144] The alloy after corrosion in this embodiment can clearly show the organizational morphology of GH3536 alloy; among them, the horizontal organizational and vertical organizational scanning images are similar to Figure 4 similar.
[0145] Example 6
[0146] This embodiment provides a corrosion method for alloys, comprising the following steps:
[0147] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0148] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic corrosion, and are taken out after the end to obtain an electrolytic corrosion sample; wherein the electrolyte includes 60 mL of perchloric acid; 60 mL of high-grade pure hydrochloric acid; and 480 mL of analytical grade anhydrous ethanol.
[0149] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0150] During electrolytic corrosion, a voltage-stabilized output mode is used, wherein the voltage is 6V, the current is 0.6A, and the electrolytic corrosion time is 10s.
[0151] The electrolytic corrosion sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0152] The alloy after corrosion in this embodiment can clearly show the organizational morphology of GH3536 alloy; among them, the horizontal organizational and vertical organizational scanning images are similar to Figure 4 similar.
[0153] Comparative Example 5
[0154] This comparative example provides a corrosion method for an alloy, comprising the following steps:
[0155] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0156] The polished sample is placed in a chemical etchant for chemical immersion corrosion to obtain a chemical corrosion sample; wherein the chemical etchant includes: 20g CuSO4, 100mL high-grade pure hydrochloric acid, 5mL high-grade pure sulfuric acid, and 80mL water; the chemical immersion corrosion time is 20s.
[0157] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0158] The chemically corroded sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0159] The scanning image of the alloy after corrosion in this comparative example is as follows: Figure 5 As shown, it can be seen that the corrosion effect is not good. This is because the grain size of the GH3536 alloy is finer and it is difficult to corrode.
[0160] Comparative Example 6
[0161] This comparative example provides a corrosion method for an alloy, comprising the following steps:
[0162] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0163] The polished sample is placed in a chemical etchant for chemical immersion corrosion to obtain a chemical corrosion sample; wherein the chemical etchant includes: 50 g of CuSO4, 100 mL of high-grade pure hydrochloric acid, and 100 mL of analytical grade anhydrous ethanol; the chemical immersion corrosion time is 10 s.
[0164] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0165] The chemically corroded sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0166] The corrosion effect of the alloy after corrosion in this comparative example is not good. Figure 5 similar.
[0167] Comparative Example 7
[0168] This comparative example provides a corrosion method for an alloy, comprising the following steps:
[0169] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0170] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic corrosion, and are taken out after the end to obtain an electrolytic corrosion sample; wherein the electrolyte includes 60 mL of perchloric acid; 60 mL of high-grade pure hydrochloric acid; and 480 mL of analytical grade anhydrous ethanol.
[0171] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0172] During electrolytic corrosion, a voltage-stabilized output mode is used, wherein the voltage is 2V, the current is 0.6A, and the electrolytic corrosion time is 5s.
[0173] The electrolytic corrosion sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0174] The surface of the alloy after corrosion in this comparative example is still in a polished state, and there are no grains and grain boundaries inside the alloy. This is because the voltage value during the electrolytic corrosion process does not meet the standard, the corrosion time is short, and the potential difference formed by the anode and cathode is not enough to form a loop, that is, the current in the loop does not reach the standard for corroding the sample, so the corrosion state is not reached after the corrosion is completed.
[0175] Comparative Example 8
[0176] This comparative example provides a corrosion method for an alloy, comprising the following steps:
[0177] The alloy is cut into a set size, and then the cut alloy is polished on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; then the alloy after the polishing is polished on the automatic grinding and polishing machine using a water-soluble polishing paste with a particle diameter of 2.5 μm; wherein the set size is 15 mm×15 mm×15 mm;
[0178] The polished alloy is used as an anode connected to the positive electrode of a DC regulated power supply, and the nickel sheet is used as a cathode connected to the negative electrode of the DC regulated power supply; the anode and the cathode are immersed in an electrolyte at the same time for electrolytic corrosion, and are taken out after the end to obtain an electrolytic corrosion sample; wherein the electrolyte includes 60 mL of perchloric acid; 60 mL of high-grade pure hydrochloric acid; and 480 mL of analytical grade anhydrous ethanol.
[0179] The alloy is a GH3536 alloy obtained by a laser powder bed fusion forming method; in terms of mass percentage, the chemical composition of the GH3536 alloy includes: C: 0.08wt.%, Cr: 21.75wt.%, Co: 1.50wt.%, W: 0.6wt.%, Mo: 9.00wt.%, Al: 0.03wt.%, Ti: 0.12wt.%, Fe: 18.50wt.%, and the balance is Ni;
[0180] During electrolytic corrosion, a voltage-stabilized output mode is used, wherein the voltage is 16V, the current is 0.6A, and the electrolytic corrosion time is 20s.
[0181] The electrolytic corrosion sample is cleaned with alcohol and blown dry to obtain a completely corroded alloy, which can be used for metallographic analysis.
[0182] The scanning image of the alloy after corrosion in this comparative example is as follows: Figure 6 As shown, it can be seen that pitting occurs inside the alloy and precipitation phases are observed at the grain boundaries. This is because the voltage value is too high and the corrosion time is too long during electrolytic corrosion, resulting in excessive corrosion and the precipitated phases at the grain boundaries falling off.
[0183] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.
[0184] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.
Claims
1. An electrolyte for alloy, characterized in that: The electrolyte is used for electrolytic polishing or electrolytic corrosion of the alloy; the electrolyte includes perchloric acid, hydrochloric acid and anhydrous ethanol; Wherein, in terms of volume, the perchloric acid is 50 to 60 parts, the hydrochloric acid is 50 to 60 parts, and the anhydrous ethanol is 400 to 480 parts.
2. The electrolyte for alloy according to claim 1, characterized in that: In the electrolyte, the volume ratio of perchloric acid, hydrochloric acid and anhydrous ethanol is 1:1:7.5-8.5; and / or The mass concentration of the perchloric acid is 70% to 72%; and / or The mass concentration of the hydrochloric acid is 36% to 38%; preferably, the hydrochloric acid is high-grade pure hydrochloric acid; and / or The mass concentration of anhydrous ethanol is ≥ 99.7%; preferably, the anhydrous ethanol is analytical grade anhydrous ethanol; and / or The alloy is GH3536 alloy; preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method.
3. A polishing method for alloy, characterized in that: The following steps are involved: placing the alloy in an electrolyte for electrolytic polishing; The alloy is used as an anode and a nickel sheet is used as a cathode; Preferably, the electrolyte is the electrolyte for alloy according to claim 1 or 2.
4. The polishing method for alloy according to claim 3, characterized in that: The alloy is GH3536 alloy; Preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method; Preferably, the chemical composition of the GH3536 alloy includes, by mass percentage: C: 0.05wt.%~0.15wt.%, Cr: 20.50wt.%~23.00wt.%, Co: 0.50wt.%~5.50wt.%, W: 0.2wt.%~1.00wt.%, Mo: 8.00wt.%~10.00wt.%, Al≤0.05wt.%, Ti≤0.15wt.%, Fe: 17.00wt.%~20.00wt.%, and the balance is Ni.
5. The polishing method for alloy according to claim 4, characterized in that: The electrolytic polishing adopts a voltage-stabilized output mode; Preferably, the voltage is 24-28V and the current is 1.0-2.0A; Preferably, the electrolytic polishing time is 10 to 15 seconds.
6. The polishing method for alloy according to any one of claims 3 to 5, characterized in that: The polishing method is used to perform structural analysis on the alloy; and / or Before the electrolytic polishing step, the method further includes: cutting the alloy into a set size and then performing a grinding process; Preferably, the set size is (15-30) mm×(15-30) mm×(15-30) mm; Preferably, the grinding process includes: on an automatic grinding and polishing machine, using 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, 3000 mesh sandpaper to grind the cut alloy in sequence until there is no oxide scale and scratches on the surface of the alloy.
7. A corrosion method for alloys, characterized in that: The following steps are involved: Placing the alloy in an electrolyte for electrolytic corrosion; The alloy is used as an anode and a nickel sheet is used as a cathode; Preferably, the electrolyte is the electrolyte for alloy according to claim 1 or 2.
8. The corrosion method for alloy according to claim 7, characterized in that: The alloy is GH3536 alloy; Preferably, the GH3536 alloy is obtained by laser powder bed fusion forming method; Preferably, the chemical composition of the GH3536 alloy includes, by mass percentage: C: 0.05wt.%~0.15wt.%, Cr: 20.50wt.%~23.00wt.%, Co: 0.50wt.%~5.50wt.%, W: 0.2wt.%~1.00wt.%, Mo: 8.00wt.%~10.00wt.%, Al≤0.05wt.%, Ti≤0.15wt.%, Fe: 17.00wt.%~20.00wt.%, and the balance is Ni.
9. The corrosion method for alloy according to claim 8, characterized in that: The electrolytic corrosion adopts a voltage-stabilized output mode; Preferably, the voltage is 5 to 8 V; the current is 0.5 to 0.8 A; Preferably, the electrolytic corrosion time is 5 to 10 seconds.
10. The corrosion method for alloy according to any one of claims 7 to 9, characterized in that: The corrosion method is used to perform structural analysis on the alloy; and / or Before the electrolytic corrosion step, the method further includes: cutting the alloy into a set size, and then performing grinding and polishing in sequence; Preferably, the set size is (15-30) mm×(15-30) mm×(15-30) mm; Preferably, the grinding process comprises: grinding the cut alloy on an automatic grinding and polishing machine using sandpaper of 180 mesh, 400 mesh, 1000 mesh, 2000 mesh, and 3000 mesh in sequence until there is no oxide scale and scratch on the surface of the alloy; Preferably, the polishing process comprises: polishing the alloy after the grinding process on an automatic grinding and polishing machine using a water-soluble polishing paste; further preferably, the particle diameter of the water-soluble polishing paste is 2 to 3 μm.